Tumor Necrosis Factor‐α Induced Apoptosis in U937 Cells Promotes Cathepsin D‐Independent Stefin B Degradation. Issue 12 (20th June 2017) - Bidovec, Katja; Božič, Janja; Dolenc, Iztok; Turk, Boris; Turk, Vito; Stoka, Veronika
ABSTRACT: Lysosomal cathepsins were previously found to be involved in tumor necrosis factor‐α (TNFα)‐induced apoptosis. However, there are opposing views regarding their role as either initiators or amplifiers of the signaling cascade as well as the order of molecular events during this process. In this study, we investigated the role of cathepsin D (catD) in TNFα/cycloheximide‐induced apoptosis in U937 human monocytic cells. TNFα‐induced apoptosis proceeds through caspase‐8 activation, processing of the pro‐apoptotic molecule Bid, mitochondrial membrane permeabilization, and caspase‐3 activation. The translocation of lysosomal catD into the cytosol was a late event, suggesting that lysosomal membrane permeabilization and the release of cathepsins are not required for the induction of apoptosis, but rather amplifies the process through the generation of reactive oxygen species. For the first time, we show that apoptosis is accompanied by degradation of the cysteine cathepsin inhibitor stefin B (StfB). CatD did not exhibit a crucial role in this step. However, this degradation was partially prevented through pre‐incubation with the antioxidant N‐acetyl cysteine, although it did not prevent apoptosis and its progression. These results suggest that the degradation of StfB, as a response to TNFα, could induce a cell death amplification effect as a result of progressive damage to lysosomes during TNFα treatment. J. Cell. Biochem. 118: 4813–4820, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Our studies show that in U937 human monocytic cells, TNFα‐induced apoptosis proceeds through caspase‐8 activation, processing of the pro‐apoptotic molecule Bid, mitochondrial and lysosomal membrane permeabilization, and caspase‐3 activation. Moreover, we firstly show that degradation of the cysteine cathepsin inhibitor stefin B could induce a cell death amplification effect as a result of progressive damage to lysosomes during TNFα treatment.